Activity of St. Casimir society in in Vilnius region (1916-1940) - Ereminas, Gintautas (Genocidas ir rezistencija, 2016)
The subject of the research is the educational work of the Lithuanian Society of St. Casimir in the difficult conditions of the Polish-ruled Vilnius region. Based on the materials of the Lithuanian Society of St. Casimir in the Manuscripts Department of the Wroblewski Library of the Lithuanian Academy of Sciences, the aim is to reconstruct the activities of the Society in the Vilnius region.